Leadership style of managers and university organisational management - Juárez, Elvis Isidro (2022)
The doctoral Thesis have main propose study the relationship to style of leadership with organizational management in the universities of south of Perú, 2020. The research had a quantitative methodology of type basic level, non- experimental -correlational. The main population was 186 directors and teachers from the universities in study. The sample consisted of 123 managers and teachers; the sampling was stratified. Used was tecnique the survey. We were two questionnaires were developed to measure the relationship between the leadership of the directors and the organizational management. The main results reveal the confirmation of the hypothesis raised in the relationship of the leadership of the directors and the university organizational management in the south region of Peru, 2020, with a p-value = 0.000 <0.05. It was concluded that there is a positive and significant correlation between the leadership of managers and organizational management.